Predicting fetoplacental mosaicism during cfDNA-based NIPT. Issue 2 (April 2020) - Neofytou, Maria
Abstract : Purpose of review: Cell-free DNA-based noninvasive prenatal testing (cfDNA-based NIPT) using maternal blood is highly sensitive for detecting fetal trisomies. However, false-positive and false-negative results can occur, which prevents NIPT from being a diagnostic test. Fetoplacental mosaicism is one of the main reasons for discordant test results. It is therefore important to understand this phenomenon to enable more comprehensive and appropriate genetic counselling. The present review aims to summarize the current knowledge of fetoplacental mosaicism ascertained during cfDNA-based NIPT and refers to the development of recent analytical pipelines for its detection during pregnancy. Recent findings: Publications are emerging demonstrating that genome-wide approaches to analyzing cfDNA can detect chromosomal aneuploidy other than the common trisomies. Despite the high accuracy of current cfDNA-based NIPT, a substantial number of false-positive and false-negative test results remain. Biological causes, such as fetal or (confined) placental mosaicism have been identified using advanced bioinformatics algorithms. Fetoplacental mosaicism can occur as part of normal pregnancy development, hence clinical practice standards recommend confirmation of positive NIPT results with a diagnostic karyotype or microarray study. Summary: cfDNA-based NIPT for fetal chromosomal aneuploidies is not diagnostic because of false-positive and false-negative test results. Recently, novel algorithms have been described that identify pregnancies with an increased risk of fetoplacental mosaicism. Reporting the presence of fetoplacental mosaicism during pregnancy can influence risk estimation and improve genetic counseling.